Liars falsehoods and free speech in an age of deception - Sunstein, Cass R. (Inalienable rights, 2021)
Liars are causing devastating problems. They are endangering public health. They are threatening self-government. They are destroying the reputation of good people - and inflating the reputation of people who are not so good. Nonetheless, falsehoods ought not to be censored or regulated, even if they are lies. Free societies allow them. Public officials should not be allowed to act as the truth police. A key reason is that we cannot trust officials to separate truth from falsehood; their own judgments are unreliable, and their own biases get in the way. If officials are licensed to punish falsehoods, they will end up punishing dissent. The best response to falsehoods is usually to correct them, rather than to punish or censor them. At the same time, governments should have the power to regulate the most harmful lies and falsehoods. In brief: False statements are not constitutionally protected if the government can show that they threaten to cause serious harm. Public officials should be able to restrict and punish lies and falsehoods that pose serious threats to public health and safety. To protect the democratic process, public officials should be able to restrict certain lies and falsehoods. They should be able to safeguard people's reputations. Private institutions, including television networks, magazines, and newspapers, and social media platforms such as Facebook and Twitter, should be doing much more to slow or stop the spread of lies and falsehoods"--